An Impartial Umpire : Industrial Relations and the Canadian State 1900-1911 - Thwaites, James (Relations Industrielles / Industrial Relations, 1982)
This article reviews the book, "An Impartial Umpire : Industrial Relations and the Canadian State 1900-1911," by Paul Craven.

Les enseignants et le pouvoir : histoire de l’Alliance des professeurs de Montréal, les luttes syndicales et le développement social (1952-1958) - Thwaites, James (Relations Industrielles / Industrial Relations, 1982)
This article reviews the book, "Les enseignants et le pouvoir : histoire de l’Alliance des professeurs de Montréal, les luttes syndicales et le développement social (1952-1958)," by Paulette Vigeant-Galley.